How is the Epistemology for E-learning Education? - UNAM, SUAyED; Elenes, Evelyn (IJRDO- Journal of Educational Research, 2017)
This article works over the conception of an educative model for E-learning University named Friendship Politics that is an effort to resolve in such a way the problem of Fruststrated Carreers in E learning Universitarians. For arriving here, the argumentation departs from making a difference in the way that learn Face to Face Scholars in relation to E-learners.